Polymorphonuclear neutrophils as accessory cells for T-cell activation: major histocompatibility complex class II restricted antigen-dependent induction of T-cell proliferation - Radsak, Markus Philipp; Iking-Konert, Christof; Stegmaier, Sabine; Andrassy, Konrad; Hänsch, Gertrud Maria (Immunology, 2000)
Polymophonuclear cells (PMN) of healthy donors do not express major histocompatibility complex (MHC) class II antigens or the T-cell costimulatory molecules CD80 or CD86. Expression of these receptors, however, is seen in patients with chronic inflammatory diseases. We now report that, by culturing PMN of healthy donors with autologous serum, interferon-gamma (IFN-gamma) and granulocyte-macrophage colony-stimulating factor (GM-CSF), de novo synthesis of MHC class II, CD80 and CD86 could be induced. MHC class II-positive PMN acquired the capacity to present staphylococcus enterotoxin to peripheral T cells, apparent as induction of interleukin-2 (IL-2) synthesis and proliferation of the T cells. Moreover, the PMN also processed tetanus toxoid (TT) and induced proliferation of TT-specific T cells in a MHC class II-restricted manner. Taken together, these data indicate that PMN can be activated to function as accessory cells for T-cell activation.